(untitled) (Sains Humanika, 2015)
The deconstructivist thoughts of the early 1980s architecture were carried out by architects who believe in change, possibility, and limitlessness. Their rebellion to what is conventional has fundamentally contributed in formulating the 21st century architecture where one of the key differences between them and others is the methodology of design. This paper addresses Zaha Hadidâ€™s strategy as a significant pioneer in this movement who has large followership around the world from among architects and designers. A qualitative study is conducted using content analysis for her accessible texts and videos as a reliable source of data. Hadidâ€™s sequential procedures of design imply that she perceives architecture as an art which could be sufficiently employed to fulfill the requirements of a good architecture and clientele.Â